#### Chemical Equations Balanced on 01/05/12

 Equations balanced on the previous day Equations balanced on the next day
 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 339 340 341 342
H2 + N2 = NH3 =>
3 H2 + N2 = 2 NH3

H2 + N2 = NH3 =>
3 H2 + N2 = 2 NH3

SO2(g) + O2(g) = SO3(g) =>
2 SO2(g) + O2(g) = 2 SO3(g)

Fe3(s) + F(g) = Fe3F =>
Fe3(s) + F(g) = Fe3F

Hg(OH)2 + Al2(CO3)3 = HgCO3 + Al(OH)3 =>
3 Hg(OH)2 + Al2(CO3)3 = 3 HgCO3 + 2 Al(OH)3

C5H9O + O2 = CO2 + H2O =>
4 C5H9O + 27 O2 = 20 CO2 + 18 H2O

Hg2CO3 = Hg + HgO + CO2 =>
Hg2CO3 = Hg + HgO + CO2

Sb + O2 = Sb4O6 =>
4 Sb + 3 O2 = Sb4O6

NaOH + H2(SO4) = Na2SO4 + H2O =>
2 NaOH + H2(SO4) = Na2SO4 + 2 H2O

SnO2 + H2 = Sn + H2O =>
SnO2 + 2 H2 = Sn + 2 H2O

Na2SO3 + HCl = NaCl + H2O + SO2 =>
Na2SO3 + 2 HCl = 2 NaCl + H2O + SO2

P4 + O2 = P2O5 =>
P4 + 5 O2 = 2 P2O5

KClO3 = K2 + ClO3 =>
2 KClO3 = K2 + 2 ClO3

N2 + H2 = NH3 =>
N2 + 3 H2 = 2 NH3

Zn(NO3)2 + K4Fe(CN)6 = KNO3 + Zn2Fe(CN)6 =>
2 Zn(NO3)2 + K4Fe(CN)6 = 4 KNO3 + Zn2Fe(CN)6

NH3 + O3 = NO2 + H2O =>
6 NH3 + 7 O3 = 6 NO2 + 9 H2O

H2 + O2 = H2O =>
2 H2 + O2 = 2 H2O

PCl5 + H2O = HCl + H3PO4 =>
PCl5 + 4 H2O = 5 HCl + H3PO4

H2SO3 + Ca(OH)2 = Ca(SO3) + H2O =>
H2SO3 + Ca(OH)2 = Ca(SO3) + 2 H2O

SO2 + O2 = SO3 =>
2 SO2 + O2 = 2 SO3

Zn(NO3)2 + K4Fe(CN)6 = KNO3 + Zn2Fe(CN)6 =>
2 Zn(NO3)2 + K4Fe(CN)6 = 4 KNO3 + Zn2Fe(CN)6

Si + CO2 = SiC + SiO2 =>
2 Si + CO2 = SiC + SiO2

Ca(OH)2 + (NH4)2SO4 = CaSO4 + H2O + NH3 =>
Ca(OH)2 + (NH4)2SO4 = CaSO4 + 2 H2O + 2 NH3

Mg + HCl = H2 + MgCl2 =>
Mg + 2 HCl = H2 + MgCl2

NaCl + F2 = NaF + Cl2 =>
2 NaCl + F2 = 2 NaF + Cl2

H2SO4 + NH4OH = H2O + (NH4)2SO4 =>
H2SO4 + 2 NH4OH = 2 H2O + (NH4)2SO4

NH3 + O2 = NO + H2O =>
4 NH3 + 5 O2 = 4 NO + 6 H2O

NH3 + O2 = NO2 + H2O =>
4 NH3 + 7 O2 = 4 NO2 + 6 H2O

Fe + H2O = Fe3O4 + H2 =>
3 Fe + 4 H2O = Fe3O4 + 4 H2

C2H6 + O2 = H2O + CO2 =>
2 C2H6 + 7 O2 = 6 H2O + 4 CO2

CH3OH + O2 = CO2 + H2O =>
2 CH3OH + 3 O2 = 2 CO2 + 4 H2O

Mg3N2 = Mg + N2 =>
Mg3N2 = 3 Mg + N2

Xe + F2 = XeF6 =>
Xe + 3 F2 = XeF6

Ca(OH)2 + H3PO4 = Ca3(PO4)2 + H2O =>
3 Ca(OH)2 + 2 H3PO4 = Ca3(PO4)2 + 6 H2O

P + O2 = P2O5 =>
4 P + 5 O2 = 2 P2O5

AgNO3 + K2CrO4 = Ag2CrO4 + KNO3 =>
2 AgNO3 + K2CrO4 = Ag2CrO4 + 2 KNO3

C24H50 + O2 = CO2 + H2O =>
2 C24H50 + 73 O2 = 48 CO2 + 50 H2O

SO3(g) + H2O(l) = H2SO4 =>
SO3(g) + H2O(l) = H2SO4

O2 + C6H14 = H2O + CO2 =>
19 O2 + 2 C6H14 = 14 H2O + 12 CO2

Zn + H2SO4 = ZnSO4 + H2 =>
Zn + H2SO4 = ZnSO4 + H2

N2 + H2 = NH3 =>
N2 + 3 H2 = 2 NH3

Ca + H2O = Ca(OH)2 + H2 =>
Ca + 2 H2O = Ca(OH)2 + H2

Cu + AgNO3 = Cu(NO3)2 + Ag =>
Cu + 2 AgNO3 = Cu(NO3)2 + 2 Ag

Pb(OH)2 + HCl = H2O + PbCl2 =>
Pb(OH)2 + 2 HCl = 2 H2O + PbCl2

Ba(NO3)2 + Na2SO4 = BaSO4 + NaNO3 =>
Ba(NO3)2 + Na2SO4 = BaSO4 + 2 NaNO3

Fe(OH)3 + H2SO4 = Fe2(SO4)3 + H2O =>
2 Fe(OH)3 + 3 H2SO4 = Fe2(SO4)3 + 6 H2O

CuO + H2SO4 = CuSO4 + H2O =>
CuO + H2SO4 = CuSO4 + H2O

N(H)4N(O)3 = (N)2O + (H)2O =>
N(H)4N(O)3 = (N)2O + 2 (H)2O

N2 + O2 = N2O =>
2 N2 + O2 = 2 N2O

Zn + FeCl3 = ZnCl2 + Fe =>
3 Zn + 2 FeCl3 = 3 ZnCl2 + 2 Fe

 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 339 340 341 342